Analisis Kepuasan Nasabah Bank Kovensional Dan Bank Syariah Di Sumatera Barat - Jean Elikal Marna; Menik Kurnia Siwi; Annur Fitri Hayati (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
Islamic banking in Indonesia is experiencing rapid development. This study aims to analyze bank customer satisfaction with services provided by conventional banks and Islamic banks. Bank satisfaction is measured through several factors including tangibles, reliability, responsiveness, assurance and empathy. The sample in this study were 100 respondents. This research method is a descriptive method using TCR analysis techniques. The results of this study indicate that TCR values in conventional banks do not have too high differences. Conventional banks have a TCR value of 0.35% higher than Islamic banks.